ChemInform Abstract: Arc‐Melting to Narrow the Bandgap of Oxide Semiconductors. Issue 31 (August 2015) - Ou, Gang; Li, Dongke; Pan, Wei; Zhang, Qinghua; Xu, Ben; Gu, Lin; Nan, Cewen; Wu, Hui
Abstract The band gaps of oxide semiconductors including Cu2O, ZnO, Y2O3, ZrO2, Nb2O5, In2O3, SnO2, GeO2, and WO3 are reduced significantly after rapid arc‐melting followed by cooling to room temperature within a few seconds.